The Influence of Factors Affecting Labor Productivity on Gold Jewelry Crafts in Karang Pule Village, Sekarbela, Mataram - Silmi Firdaus; Helmy Fuadi; Vici Handaluisa Husni (Tinta Emas Publisher, 2024)
This research aims to analyze the influence of education, age, wages and length of work on labor productivity in gold jewelry crafts in Karang Pule Village, Sekarbela Environment, Mataram City. This type of research is quantitative descriptive. Testing was carried out on 51 respondents spread across three neighborhoods in Karang Pule Village, namely, West Pande Mas, East Pande Mas, and Pande Besi. The data used in this research is primary data obtained by distributing questionnaires to respondents. The analytical tools used are multiple linear regression, simultaneous determination test (R2), t test, and simultaneous regression coefficient significance test (F test). The results of the analysis show that the variables education, age, wages and length of work together (simultaneously) have a positive and significant effect on labor productivity in gold jewelry crafts in the Sekarbela area, Karang Pule sub-district with a significant value of 0.000 < 0.05. Individually (partially), the Wage and Length of Work variables on Gold Jewelry Crafts in the Sekarbela Environment, Karang Pule Subdistrict have a positive and significant effect on labor productivity, with a significant value of 0.000 < 0.05, while the education and age variables have a positive but not significant effect on labor productivity in Gold Jewelry Crafts in the Sekarbela Environment, Karang Pule Village with a significant value of 0.126 > 0.05 for education and 0.194 > 0.05 for age.